Drought stress and recovery of mango and citrus plants - Iberahim, Ismail; Ismail, Mohd Razi (2001)
Drought stress has reduced photosynthesis rate and stomatal conductance of mango and citrus plants. After 6 days under drought stress the value of physiological responses was reduced more than 50%. Citrus plants showed high peroxidase activity compared to mango plants. High peroxidase gave ability for faster recovery than plants with low peroxidase activity.